Impacto social de la preparación física en combatientes del MININT (Revisión) (Revista científica Olimpia, 2022)
The high physical preparation of the MININT agents is important for the development of their combative activity, for this reason the training institution prepares them to satisfy the physical competencies inherent to the basic profile. This physical preparation is part of the combat preparation system of the officers who are trained in the military education centers. Physical preparation is an activity that requires, on the part of the combatant in training, high physical resistance, strength, agility, speed in actions, mastery necessary for overcoming obstacles, carrying out the elements of attack and self-defense, strengthening health and temperance, the ability to act accurately in conditions of physical and mental stress, as well as limited mobility, educates boldness, decision, initiative, confidence in their strength, a sense of collectivism and help mutual between combatants. However, there are difficulties that negatively affect that physical preparation that affect the social order, among them: there is no manual of physical preparation, the study programs address physical preparation from a general approach, not particularized, students present deficiencies in the physical capacities that are controlled and evaluated from the Personal Defense course. For this reason, this work is carried out, with the aim of analyzing the need to encourage the development of physical preparation in MININT combatants, to contribute to the effective fulfillment of missions related to their social mandate.